Ruby Lu, empress of everything - Look, Lenore (Atheneum Books for Young Readers, 2006)
After Ruby Lu's deaf cousin, Flying Duck, and her parents come from China to live with her, Ruby finds life challenging as she adjusts to her new family, tries to mend her rocky relationship with her friend Emma, and faces various adventures in summer school.